"It Just Consumes Your Life": Quality of Life for Informal Caregivers of Diverse Older Adults With Late-Life Disability. (August 2016) - Thai, Julie N.; Barnhart, Caroline E.; Cagle, John; Smith, Alexander K.
Little is known about the quality of life (QoL) for informal caregivers of disabled older adults aged 65+ with diverse backgrounds. Forty-two caregivers were interviewed in English and Cantonese about their caregiving experiences, their recollections of QoL over time, and the factors influencing their appraisals. Overall, 52% of caregivers experienced a decline in QoL. Factors associated with decreased QoL were less time for self, competing financial demands, and the physical and emotional impact of the patient's illness. Factors associated with no change in QoL were minimal caregiving responsibilities, a sense of filial duty, and QoL being consistently poor over time. Factors associated with improved QoL were perceived rewards in caregiving, receiving institutional help, and increased experience. Chinese caregivers were more likely to cite filial duty as their motivator for continued caregiving than were Caucasian caregivers. In conclusion, informal caregivers take on a huge burden in enabling older adults to age in the community. These caregivers need more support in maintaining their QoL.